1954
DOI: 10.1111/j.1476-5381.1954.tb00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Mast Cell Fragmentation by Compound 48/80

Abstract: Compound 48/80 as reported by Baltzly, Buck, de Beer, and Webb (1949) All solutions were at room temperature. Usually two pieces of mesentery were used in each concentration of drug. From these pieces five microscope fields were selected at random under 100 x magnification from widely separated areas of the mesentery. In each field, using 430 x magnification, the first 10 mast cells were examined, starting from the lefthand side of the field and proceeding clockwise. For each drug concentration 50 cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1956
1956
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…After an incubation period of 10 minutes, the tissues were removed, trimmed and stained with 1.0% toluidine blue solution and examined microscopically for the number of intact and de-granulated mast cells. A mast cell was considered disrupted if four or five granules were observed around the mast cells as reported by Norton (1954).…”
Section: Evaluation Of Mast Cell Stabilizing Activity Active Anaphylaxismentioning
confidence: 99%
“…After an incubation period of 10 minutes, the tissues were removed, trimmed and stained with 1.0% toluidine blue solution and examined microscopically for the number of intact and de-granulated mast cells. A mast cell was considered disrupted if four or five granules were observed around the mast cells as reported by Norton (1954).…”
Section: Evaluation Of Mast Cell Stabilizing Activity Active Anaphylaxismentioning
confidence: 99%
“…The tissue was first immersed in 0.1% toludine blue (in 4% aqueous saline) for 10 minutes [12]. 10.The tissue was then treated with xylene for 5-10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…[19] In the present investigation, the authors have tried to assess the in vitro mast cell stabilization studies of the extracts ZXE and ZXA observed a significant dose dependant reduction (p<0.001) in mast cell degranulation when compared to C48/80. ZXE extracts (68.8 ± 2.7) demonstrated dose dependent highest mast cell stabilization ability in rat mesentery preparation.…”
Section: Insights In Allergy Asthma and Bronchitis Issn 2471-304xmentioning
confidence: 99%
“…A mast cell was considered disrupted if 4 or 5 granules were found around the mast cells. The percentage of mast cell fragmented or disrupted and of intact mast cells was calculated [18,19].…”
Section: Mast Cell Stabilization Activitymentioning
confidence: 99%